Can AI Improve Supply Chain Management in Healthcare? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The healthcare industry grapples with immense pressure to deliver high-quality patient care while simultaneously managing escalating costs. An often-overlook...
Keywords: Healthcare Administration and AI; Improve; Supply; Chain; Artificial Intelligence; Machine Learning; Healthcare